2015
DOI: 10.1080/03605302.2015.1025979
|View full text |Cite
|
Sign up to set email alerts
|

A Morse Index Theorem for Elliptic Operators on Bounded Domains

Abstract: Abstract. Given a selfadjoint, elliptic operator L, one would like to know how the spectrum changes as the spatial domain Ω ⊂ R d is deformed. For a family of domains {Ωt} t∈ [a,b] we prove that the Morse index of L on Ωa differs from the Morse index of L on Ω b by the Maslov index of a path of Lagrangian subspaces on the boundary of Ω. This is particularly useful when Ωa is a domain for which the Morse index is known, e.g. a region with very small volume. Then the Maslov index computes the difference of Mors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
92
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(93 citation statements)
references
References 23 publications
1
92
0
Order By: Relevance
“…In [3] the first author, Kuchment and Smilansky gave an explicit formula for the nodal deficiency as the Morse index of an energy functional defined on the space of equipartitions of Ω. More recently [6], the second two authors, with Jones, computed the nodal deficiency in terms of the spectra of Dirichlet-to-Neumann operators using Maslov index tools developed in [7,5]. In particular, for a simple eigenvalue λ k , it was shown that δ(φ k ) = Mor (Λ + ( ) + Λ − ( )) (2) for sufficiently small > 0, where Λ ± ( ) denote the Dirichlet-to-Neumann maps for the perturbed operator ∆ + (λ k + ), evaluated on the positive and negative nodal domains Ω ± = {±φ k > 0}, and Mor denotes the Morse index, or number of negative eigenvalues.…”
Section: Introductionmentioning
confidence: 99%
“…In [3] the first author, Kuchment and Smilansky gave an explicit formula for the nodal deficiency as the Morse index of an energy functional defined on the space of equipartitions of Ω. More recently [6], the second two authors, with Jones, computed the nodal deficiency in terms of the spectra of Dirichlet-to-Neumann operators using Maslov index tools developed in [7,5]. In particular, for a simple eigenvalue λ k , it was shown that δ(φ k ) = Mor (Λ + ( ) + Λ − ( )) (2) for sufficiently small > 0, where Λ ± ( ) denote the Dirichlet-to-Neumann maps for the perturbed operator ∆ + (λ k + ), evaluated on the positive and negative nodal domains Ω ± = {±φ k > 0}, and Mor denotes the Morse index, or number of negative eigenvalues.…”
Section: Introductionmentioning
confidence: 99%
“…Smale's result, which only applies to the Dirichlet problem, was originally proved by variational methods (see also [25]). A proof using the Maslov index was given in [9] for star-shaped domains, and in [7] for the general case.…”
Section: Remarkmentioning
confidence: 99%
“…In this paper we give a symplectic formulation of this problem, and use it to prove a constrained version of the celebrated Morse-Smale index theorem. We begin by reviewing the symplectic formulation of the unconstrained spectral problem, which first appeared in [9], and was elaborated on in [6,7]. Hypothesis 1.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations